Generation of IPv6 addresses based on one-to-many reversible mapping using AES - Hakiem, Nashrul; Priantoro, Akhmad Unggul; Siddiqi, Mohammad Umar; Hasan, Talib Hashim (Springer-Verlag, 2012)
The proliferation of enterprise wireless network raises the security concern in any organization despite the unarguable benefits it brings about. At the same time, the initiative to migrate from IPv4 (Internet Protocol version four) to IPv6 (Internet Protocol version six) is gaining momentum across the globe to resolve the IP address depletion problem as well as reaping the benefit of it. This research proposes a new scheme to manage IPv6 addresses in an enterprise wireless local area network (WLAN) which may be incorporated into DHCPv6 (Dynamic Host Configuration Protocol for IPv6) software. In this scheme each user is assigned a dynamic IPv6 address that is generated cryptographically. Each time a user tries to access the network, different IPv6 address will be given which is generated using CFB (Cipher Feedback) mode of AES (Advanced Encryption Standard) algorithm, whereby there is a one-to-many reversible mapping between user and IPv6 addresses. In this way, it is possible for the network administrator to identify users in real time from their IPv6 address although a user’s IP address regularly changed. Dynamically changing IP address will impede an external network adversary’s effort to track user’s online behavior, thus enhancing privacy.